Significance of Peel Test Speed on Interface Strength in Cohesive Zone Modeling. Issue 1 (2nd January 2016) - Noori, Hadi; Jain, Mukesh; Nielsen, Kent; Brandys, Frank
Abstract : The analysis of the experimental peel test data for obtaining the adhesion fracture energy of an adhesively laminated polymer to the sheet metal surface is considered. The experimental results of the 180° peel test on two types of polymer laminated sheet metal at three different peel speeds are analyzed by two methodological approaches in cohesive zone modeling. These approaches are linear-elastic stiffness approach and critical maximum stress approach. Comparing the results of these two approaches reveals the significance of the peel test speed on the interface strength determination for cohesive zone modeling. It is concluded that a "reference" peel speed may exist at which the interface strength is equal to the yield strength of the peel arm material. A constitutive equation has been proposed which relates the interface strength to the peel test velocity by using the reference peel speed and its corresponding peel arm yield strength.